LADS: a powerful vaccine platform for cancer immunotherapy and prevention - Jing Sun; Jing Wang; Xin Jiang; Jing Xia; Yue Han; Mianmian Chen; Jiali Xu; Simin Deng; Changyong Cheng; Houhui Song (BMC Biology)
Abstract Background The intracellular bacterium Listeria monocytogenes is an attractive vector for cancer immunotherapy as it can effectively deliver tumor antigens to antigen-presenting cells, leading to a robust antitumor response. Results In this study, we developed a novel vaccine platform called Listeria-based Live Attenuated Double Substitution (LADS), which involves introducing two amino acid substitutions (N478AV479A) into the virulence factor listeriolysin O (LLO). LADS is a safe vaccine platform, with an attenuation of nearly 7000-fold, while retaining complete immunogenicity due to the absence of deletion of any virulence factors. We developed two LADS-based vaccines, LADS-E7 and LADS-AH1, which deliver the human papillomavirus (HPV) type 16 E7 oncoprotein and murine colon carcinoma immunodominant antigen AH1, respectively. Treatment with LADS-E7 or LADS-AH1 significantly inhibited and regressed established tumors, while also dramatically increasing the populations of tumor-infiltrated antigen-specific CD8+ T cells. RNA-sequencing analysis of tumor tissue samples revealed that LADS-E7 altered the expression of genes related to the immune response. Moreover, intratumoral injection of LADS-based vaccines induced strong antitumor responses, generating systemic antitumor responses to control distant tumor growth. Encouragingly, LADS-E7 or LADS-AH1 immunization effectively prevented tumor formation and growth. Conclusions Our findings demonstrate that LADS-based vaccines represent a more powerful platform for the development of immunotherapeutic and preventive vaccines against cancers and infectious diseases.